The Weak State Trap (2020)
Development outcomes come in `clusters' that seem difficult to exit. Using original data from Colombia, we present evidence of the interconnection between two critical political components: state weakness and clientelism. State weakness creates the right environment for clientelism to ourish. Clientelism sets in place a structure of incentives for politicians and citizens that is detrimental to building state capacity. We show that vote buying, as a measure of clientelism, and tax evasion, as a measure of state weakness, are highly correlated at the individual level. We also report evidence that both practices are widely accepted in society, a result consistent with a deeply entrenched relationship of mutually reinforcing in uences. Finally, we propose a set of mechanisms that underlie the hypothesis that a weak state and widespread clientelism are part of a political equilibrium with multiple feedback loops. Our results suggest that state weakness is a trap that is likely hard to exit.